Resistance of Sheikh Mohamed ELHASNAWI in the Region of Annaba in the East of Algeria (1847-1830) - rouabhi, al-Ayachi (The Algerian Historical Journal, 2026)
In the incept of the French colonization of Algeria, sheikh ELHASNWI led a violent resistance against the French colonizer in the region of Annaba, a town in the East of Algeria. This resistance extended to the year 1847. Due to his bad relationship with Elhadj Ahmed BEY, the last of the BEYS of Constantine, Sheikh ELHASNAWI served the French for a short time. Since he was not satisfied with his situation, he joined and was an assistant of Elamir ABDELKADER in this strategic region of Annaba. During his resistance, Sheikh ELHASNAWI took Tunisia as a safe refuge in the hard times. This study tries to shed some light on this resistance using different documents and sources.